Implementation of Moderate Islamic Education Values Based on Local Wisdom in Kepahiang Regency - Guntur Putrajaya; Idi Warsah; Sutarto Sutarto (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
This research examines the role of religious moderation in maintaining social harmony in Indonesia's multicultural society, with a particular focus on Kepahiang Regency, Bengkulu Province. One of the main factors that trigger conflict is radical understanding. To prevent radicalism and promote tolerance. This research explores the concept of religious moderation developed by the Indonesian Ministry of Religious Affairs. This concept emphasizes the values of nationality, tolerance, non-violence, and accommodation of local culture. This research focuses on the implementation of religious moderation through local wisdom, with case studies on the Rejang Kepahiang Traditional Institute (LARK) and the People's Welfare Section (Kesra). Local traditions such as Umbung Kutei and Kendurei, which reflect Islamic values such as gratitude, mutual cooperation (gotong royong), and tolerance, play an important role in maintaining social cohesion and preventing radicalism. The research method used is a qualitative approach with ethnographic methods, which utilizes interviews, observation, and document analysis. The results show that the synergy between local wisdom and moderate Islam can strengthen religious tolerance and prevent extremism. However, challenges such as community resistance to change and limited resources need to be overcome with strategies involving tradition-based policies, education, and periodic evaluation. This research makes a significant contribution to the understanding of religious moderation at the local level and the role of local wisdom in strengthening social harmony in multicultural societies. Penelitian ini mengkaji peran moderasi beragama dalam menjaga harmoni sosial di masyarakat multikultural Indonesia, dengan fokus khusus pada Kabupaten Kepahiang, Provinsi Bengkulu. Salah satu faktor utama yang memicu konflik adalah pemahaman radikal. Sebagai upaya untuk mencegah radikalisme dan mempromosikan toleransi. Penelitian ini mengeksplorasi konsep moderasi beragama yang dikembangkan oleh Kementerian Agama RI. Konsep ini menekankan nilai kebangsaan, toleransi, anti-kekerasan, serta akomodasi terhadap budaya lokal. Penelitian ini berfokus pada implementasi moderasi beragama melalui kearifan lokal, dengan studi kasus pada Lembaga Adat Rejang Kepahiang (LARK) dan Bagian Kesejahteraan Rakyat (Kesra). Tradisi lokal seperti Umbung Kutei dan Kendurei, yang mencerminkan nilai-nilai Islam seperti syukur, gotong royong, dan toleransi, memainkan peran penting dalam menjaga kohesi sosial dan mencegah radikalisme. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan metode etnografi, yang memanfaatkan wawancara, observasi, dan analisis dokumen. Hasil penelitian menunjukkan bahwa sinergi antara kearifan lokal dan Islam moderat mampu memperkuat toleransi beragama dan mencegah ekstremisme. Namun, tantangan seperti resistensi masyarakat terhadap perubahan dan keterbatasan sumber daya perlu diatasi dengan strategi yang melibatkan kebijakan berbasis tradisi, pendidikan, dan evaluasi berkala. Penelitian ini memberikan kontribusi signifikan terhadap pemahaman tentang moderasi beragama di tingkat lokal dan peran kearifan lokal dalam memperkuat harmoni sosial di masyarakat yang multikultural.